Application of AFLP-Method in Plant Sample Identification - Zubor, Ákos; Surányi, Gyula; Prokisch, József; Győri, Zoltán; Borbély, György (Acta Agraria Debreceniensis, 2003)
One possible method for the determination of DNA-polymorphism is the PCR-based AFLP (Amplified Fragment Length Polymorphism). This method had been succesfully introduced to the Department of Botany at University of Debrecen in 2000-2001 with the examination of hay saffron (Crocus sativus L.) and its allies. Hay saffron is grown as a spice for some thousand years producing the most expensive spice in the world. This plant is sterile, triploid reproduces only vegetatively with no fertile seeds. However its origin is unknown it exists only in cultivation and it is a mutated variety of another species or an artificial or natural hybrid. Usual methods for the systematic examination are restricted hence it seemed to be reasonable to apply molecular biological methods in its case. Results of this work include the introduction and many fold application of the method beside ensuring the consequences of science literature with determining the C. cartwrightianus to give the most similar genetical pattern to C. sativus.